Dietary supplementation with polypeptin and bioture improves growth, feed utilization, antioxidant capacity, and disease resistance in juvenile hybrid grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂) - Jing, Futao; Yin, Xianghan; Ren, Yichao; Han, Yongmei; Zhou, Qi; Xia, Bin; Li, Qiang; Liu, Peng (Frontiers in Marine Science, 2025)
Intensive aquaculture of hybrid grouper (Epinephelus spp.) is often constrained by inefficient feed conversion and recurrent outbreaks of vibriosis. This study investigated the individual and combined effects of dietary polypeptin and bioture on growth performance, physiological status, and disease resistance in juvenile hybrid grouper. A 3 × 3 factorial design was employed to formulate nine iso-nitrogenous and iso-lipidic diets (i.e., P0B0, P2B0, P4B0, P0B2, P2B2, P4B2, P0B4, P2B4, and P4B4), incorporating polypeptin and bioture at 0%, 0.2%, and 0.4% inclusion levels. Fish were fed experimental diets for 56 days, followed by a 144 h challenge with Vibrio harveyi. The results showed that co-supplementation significantly improved multiple performance indicators, exhibiting notable synergistic effects: final body weight, weight gain, and specific growth rate increased, while feed conversion ratio and hepatosomatic index decreased. Digestive enzyme activities, particularly pepsin and trypsin, were markedly elevated, indicating improved digestive efficiency. Furthermore, antioxidant capacity was significantly enhanced in co-supplemented groups, as evidenced by increased T-AOC, SOD, and CAT, coupled with reduced MDA contents. Serum biochemical parameters related to stress and hepatic function, including AST, ALT, LDH, TG, T-CHO, and cortisol, were significantly lower in supplemented groups. The levels of LZM, ACP, AKP, and IgM were significantly upregulated both at baseline and post-challenge, indicating enhanced humoral immunity. During the V. harveyi challenge, the highest survival rates were observed in P4B4, demonstrating delayed onset and reduced cumulative mortality relative to the control. In conclusion, dietary co-administration of polypeptin and bioture, particularly in the P4B4 group, elicited synergistic benefits across multiple physiological and immunological parameters, significantly enhancing growth performance, digestive function, oxidative balance, and disease resistance in juvenile hybrid grouper. These findings support the potential of precision-nutrition strategies incorporating functional feed additives for sustainable and health-optimized grouper aquaculture.